Meningkatkan Pengetahuan Atlet-Pelajar Tentang Kesehatan Mental di Sekolah Menengah Pertama Negeri 18 Kota Bengkulu - Ari Sutisyana; Nurul Fajar Muslimah Ningrum; Rita Shintia; Yahya Eko Nopiyanto (JURPIKAT, 2025)
Student-athletes, who simultaneously play both roles as students and athletes, are likely to experience increased mental health issues. Therefore, the purpose of this community service is to educate student-athletes about mental health and how to address mental health issues. A participatory, educational approach was used in this community service activity to deliver material to student-athletes. The stages of this activity consisted of preparation, implementation, and evaluation. A total of 30 student-athletes, consisting of grades VII, VIII, and IX from various sports, were involved as participants. The material was delivered on September 16, 2025. The evaluation instrument used a questionnaire distributed before and after the activity. The data analysis technique used simple quantitative descriptive analysis by observing the average score of the collected answers. The analysis results showed that before the activity, the average score was 6.97 and after the activity, it increased to 7.13. It can be concluded that this community service activity can have a positive impact on increasing student-athletes' knowledge regarding mental health issues. These results provide an important foundation for mentoring student-athletes in implementing training programs to maintain mental health